Physical and mechanical properties of concrete using fly ash and recycled concrete aggregates - Ooi, Wei Hong (2014)
In this research, physical and mechanical properties of concrete were investigated by using fly ash and recycled concrete aggregates (RCA) as partial replacement. Fly ash was collected from the Tanjung Bin Power Plant at Pontian and recycled concrete aggregates were obtained from waste at laboratory. So, 20% of total amount of cement was replaced by fly ash as partial replacement but for recycled concrete aggregates, it was replaced coarse aggregates as 0%, 25%, 50%, 75% and 100% to check which is the best combination. The dosage of superplasticizer in this study was 1.5% of weight of cement and 0.4 water/cement ratio was used in the mixture.. A number of tests were conducted to investigate fresh and hardened state properties like slump, ultrasonic pulse velocity, compressive, tensile and flexural strength of fly ash and recycled aggregates concrete. Test specimens comprising of cube, cylinder and prism were prepared and tested after 1, 7, 28 and 56 days of water curing. It was found that the workability of the concrete was reduced as the percentage of RCA increased. The range of the workability of the fresh concrete was fall at 65 mm to 130 mm. However, high content of RCA was increased the water absorption of the concrete. The result has obtained that the water absorption of concrete was in the range of 5.38% to 8.65% among the samples. A reduction on compressive, tensile and flexural strength occurred as the content of replacement increased. As conclusion, concrete with 20% of fly ash and 25% of recycled aggregates as partial replacement was concluded as the best mixed ratio since the mechanical properties of the concrete was almost equal to the conventional concrete. The maximum compressive strength of the sample was 34.55 MPa while splitting tensile strength and flexural strength have achieved 3.7 MPa and 4.35 MPa.